ANALISIS PENGGUNAAN MAJAS PADA PUISI "NOCTURNO FRAGMENT" KARYA CHAIRIL ANWAR: KAJIAN STILISTIKA - Zalfa, Fika Fauziyah; Cumana, Wafiq Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This article discusses the poem "Nocturno Fragment" by Chairil Anwar. The poem is discussed using a stylistic study, which focuses on analyzing the use of figure of speech. Stylistics is a study that discusses the use of style in a poem to present the values of beauty in the poem. The method used in this research is descriptive research with qualitative method using poetry as the source data and research object. The research was conducted by examining the stanzas and lines of the poem to determine what figure of speech is used. The results of this study indicate that in the poem "Nocturno Fragment" by Chairil Anwar, paradox, personification, hyperbole and metaphor are used. The poem describes the anxiety and frustration felt by the poet and then poured it into a poem entitled "Nocturno Fragment" which means pieces of the night. The use of figure of speech in this poem has succeeded in providing its own beauty and meaning that can be translated from various points of view.